Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a) Ta có: \(\frac{8}{40}+\frac{-4}{20}-\frac{3}{5}\)
\(=\frac{1}{5}+\frac{-1}{5}-\frac{3}{5}\)
\(=\frac{-3}{5}\)
b) Ta có: \(\frac{-7}{12}+\frac{-2}{12}-\frac{-3}{36}\)
\(=\frac{-7}{12}+\frac{-2}{12}-\frac{-1}{12}\)
\(=\frac{-9+1}{12}=\frac{-8}{12}=\frac{-2}{3}\)
c) Ta có: \(\left(\frac{1}{6}+\frac{-4}{13}\right)-\left(-\frac{17}{6}-\frac{30}{13}\right)\)
\(=\frac{1}{6}+\frac{-4}{13}+\frac{17}{6}+\frac{30}{13}\)
\(=3+2=5\)
d) Ta có: \(-\frac{-5}{4}+\frac{7}{4}-\frac{-11}{7}+\frac{2}{7}\)
\(=\frac{5}{4}+\frac{7}{4}+\frac{11}{7}+\frac{2}{7}\)
\(=3+\frac{13}{7}=\frac{21}{7}+\frac{13}{7}=\frac{34}{7}\)
e) Ta có: \(-\frac{1}{8}+\frac{-7}{9}+\frac{-7}{8}+\frac{6}{7}+\frac{2}{14}\)
\(=-1+1+\frac{-7}{9}\)
\(=-\frac{7}{9}\)
f) Ta có: \(\frac{-2}{9}-\frac{11}{-9}+\frac{5}{7}-\frac{-6}{-7}\)
\(=\frac{-2-\left(-11\right)}{9}+\frac{5-6}{7}\)
\(=1+\frac{-1}{7}=\frac{7}{7}+\frac{-1}{7}=\frac{6}{7}\)
Bài 2:
b: x+25%x=-1,25
=>1,25x=-1,25
hay x=-1
c: x-75%x=1/4
=>1/4x=1/4
hay x=1
Bài 2:
a: =3/2-11/4=6/4-11/4=-5/4
b: =-49/6-17/2=-49/6-51/6=-100/6=-50/3
Bài làm
a) \(-\frac{3}{7}+\frac{3}{4}:\frac{3}{14}\)
= \(-\frac{3}{7}+\frac{3}{4}.\frac{14}{3}\)
= \(-\frac{3}{7}+\frac{7}{2}\)
\(=-\frac{7}{14}+\frac{49}{14}\)
\(=\frac{42}{14}=3\)
b) \(5-\frac{7}{39}:\frac{7}{13}+\frac{8}{9}:4\)
\(=5=\frac{7}{39}.\frac{13}{7}+\frac{8}{9}.\frac{1}{4}\)
\(=5-\frac{1}{3}+\frac{2}{9}\)
\(=\frac{45}{9}-\frac{3}{9}+\frac{2}{9}\)
\(=\frac{44}{9}\)
c) \(\left(\frac{5}{12}:\frac{11}{6}+\frac{5}{12}:\frac{11}{5}\right)-\frac{-7}{12}\)
\(=\left(\frac{5}{12}.\frac{6}{11}+\frac{5}{12}.\frac{5}{11}\right)+\frac{7}{12}\)
\(=\left[\frac{5}{12}\left(\frac{6}{11}+\frac{5}{11}\right)\right]+\frac{7}{12}\)
\(=\frac{5}{12}+\frac{7}{12}\)
\(=\frac{12}{12}=1\)
d) \(-\frac{5}{9}+\frac{14}{9}\left(\frac{3}{4}-\frac{2}{5}\right):49\)
\(=-\frac{5}{9}+\frac{14}{9}\left(\frac{15}{20}-\frac{8}{20}\right):49\)
\(=-\frac{5}{9}+\frac{14}{9}.\frac{7}{20}.\frac{1}{49}\)
\(=-\frac{5}{9}+\frac{7}{9}.\frac{7}{10}.\frac{1}{7.7}\)
\(=-\frac{5}{9}+\frac{1}{90}\)
\(=-\frac{50}{90}+\frac{1}{90}=-\frac{49}{90}\)
a) \(\frac{2}{5}+\left(\frac{3}{4}-\frac{7}{10}\right)\)
\(=\frac{2}{5}+\frac{1}{20}\)
\(=\frac{9}{20}\)
b) \(\frac{-1}{8}-\left(\frac{2}{3}-\frac{11}{12}\right)\)
\(=-\frac{1}{8}-\left(-\frac{1}{4}\right)\)
\(=\frac{1}{8}\)
c) \(\frac{7}{5}-\left(\frac{1}{6}+\frac{9}{10}\right)\)
\(=\frac{7}{5}-\frac{16}{15}\)
\(=\frac{1}{3}\)
d) \(\frac{2}{3}+\left(-\frac{1}{4}\right)+\frac{7}{12}-\left(-\frac{1}{4}\right)-\frac{5}{6}\)
\(=\left(\frac{2}{3}+\frac{7}{12}-\frac{5}{6}\right)+\left(-\frac{1}{4}+\frac{1}{4}\right)\)
\(=\left(\frac{5}{4}-\frac{5}{6}\right)+0\)
\(=\frac{5}{12}\)
e) \(2-\left\{\frac{1}{2}-\left[2-\left(\frac{1}{2}+2\right)-\frac{1}{2}\right]+2\right\}\)
\(=2-\left[\frac{1}{2}-\left(2-\frac{5}{2}-\frac{1}{2}\right)+2\right]\)
\(=2-\left[\frac{1}{2}-\left(-1\right)+2\right]\)
\(=2-\frac{7}{2}\)
\(=-\frac{3}{2}\)
a) \(\frac{6^7}{4^3\cdot9^2}=\frac{2^7\cdot3^7}{2^6\cdot3^4}=2\cdot3^3=2\cdot27=54\)
b) \(\frac{12^3\cdot15^3}{4^3\cdot25^2\cdot9^2}=\frac{2^6\cdot3^3\cdot3^3\cdot5^3}{2^6\cdot5^4\cdot3^4}=\frac{3^2}{5}=1,8\)
c) \(\frac{2^{11}+3\cdot2^{10}}{10\cdot4^5}=\frac{2^{10}\left(2+3\right)}{2\cdot5\cdot2^{10}}=\frac{1}{2}=0,5\)
d) \(\frac{3^8\cdot2-3^6}{2\cdot17\cdot3^7}=\frac{3^6\left(3^2\cdot2-1\right)}{2\cdot17\cdot3^7}=\frac{1}{2\cdot3}=\frac{1}{6}\)